Performance of VRF systems based on large scale monitoring. Issue 5 (September 2019) - Liu, Hua; Qian, Mingyang; Yan, Da; Berardi, Umberto
Abstract: Variable Refrigerant Flow (VRF) systems are refrigerant systems, which are generally comprised of an outdoor unit serving multiple indoor units connected by a refrigerant piping network. It is important to evaluate the performance of VRF systems, which can help the design and operate of VRF systems. Performance test done by manufactory can reveal the performance of VRF systems in designed conditions. However, it is hard to reveal effective performance in real buildings. The field test is complicated compared with the test in the laboratory and can only conduct on typical samples rather than large scale samples. However, typical samples are not enough for reflecting the performance of large scale VRF systems samples. A simple method of evaluating the performance of large scale VRF systems samples is necessary. This paper proposed and calculating model for electricity consumption and cooling demand of VRF systems based on measured operating data in the laboratory. The paper used the calculating model combined with 344 samples operating data from real residential buildings to calculate the performance of a large scale VRF. This paper analyzed the VRF systems' performance with different influencing factors such as climate zones, cooling duration and outdoor temperature for the recommendation for VRF systems' designing and operation.